The Development of Characteristics Indicators of Export Market Orientation: A Case Study of Thai Processed Food Exporters - Pojsupap, Thantip (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2019)
This research objectives were to develop characteristics indicators of export market orientation (EMO). A quantitative method of analysis was employed for a total of 528 Thai processed food exporters by multistage random sampling. Data was collected using 5-point likert scales in a questionnaire with 15 items, and analyzed by first-order and second-order confirmatory factor analysis (FOCFA and SOCFA) using a structural equation modeling approach. The results demonstrated that the characteristics indicators of export market orientation consisted of three latent variables, including export market intelligence generation (ExIntel), export market intelligence dissemination (ExDiss) and export market responsiveness and coordinating mechanism (ExResp). The test of the SOCFA model implied that three latent variables were a good fit for measuring the export market orientation construct. There were several indicators of goodness-of-fit which indicated a good fit : df= 59 p = 0.000 NFI = 0.992 NNFI = 0.994 CFI = 0.997 RMSEA = 0.039 RMR = 0.029 SRMR = 0.033 GFI = 0.974 AGFI = 0.947. The composite reliability values were between 0.727 and 0.951, in which all CR values were above the suggested minimum of 0.70, and the average variance extracted values were between 0.367 and 0.866, in which most of the AVE values were above 0.50. The goodness-of-fit indices indicated that the research model was congruent to empirical data.